Dissimilarities between the national cost/benefit models of road projects : Comparing appraisals in Nordic countries - Sandberg Hanssen, Thor-Erik; Helo, Petri; Solvoll, Gisle; Westin, Jonas; Westin, Lars (Elsevier, 2020)
The Nordic Council has a vision to create the most integrated region globally by 2030. Nevertheless, Nordic cross-border infrastructure projects are generally developed by each nation individually. Joint Nordic infrastructure planning is thus fragmented. An example of this, as reported herein, is how road projects are assessed by the infrastructure planning authorities in Norway, Sweden, and Finland, the latter to which is included in the comparison for the first time. In each country, cost/benefit analyses (CBAs) are used. In each nation, the monetary values of changes in travel time, accidents, and environmental externalities are estimated. We then apply those values to the three national CBA models to assess an illustrative hypothetical road project. Theoretically, the models should provide similar outcomes when using a common set of parameters. Instead, we show that the choice of national model is crucial to the outcome. The Swedish model, for example, generates a higher cost of travel time than the other models irrespective of the nation from which we choose the parameters. Consequently, CBA-based assessments in the Nordic area depend strongly on the model applied and peculiarities in its coding. Finally, we discuss the policy implications of our findings for appraising national and Nordic projects.
Keywords: Cost/benefit analysis; Nordic transport infrastructure; Value of travel time; Value of life; Value of environment; Nordic planning models; fi=Tuotantotalous|en=Industrial Management|